Strategi Guru Paud dalam Meningkatkan Perkembangan Moral Anak Usia Dini di TK Yayasan Pendidikan Al Kamal Laud Dendang - Sandika Octovani Sitanggang; Novi Nuriana Ningsih; Pebri Romaito Banjarnahor; Revana Trisia Hasibuan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the strategies implemented by teachers at the Al Kamal Education Foundation Kindergarten in fostering the moral development of early childhood, in accordance with the standards of early childhood educators regulated in national regulations. This study uses a qualitative descriptive approach, with data collection through in-depth interviews with the principal and observations of children's play activities outside the classroom. The results of the study indicate that the main strategies used are habituation, direct practice, and integration of religious activities such as routine ablution and prayer practices. Play-based learning is also the main focus, where children are taught to share, take turns, and control emotions through various games such as playing blocks and swings. This study also highlights the importance of the role of parents in moral education.